Thomas Herbst and Kerstin Popp (Editors). The Perfect Learners' Dictionary (?). - Abecassis, Michaël (Lexikos, 2006)
This collection of articles originates from a 1997 symposium in which participated some of the most eminent scholars researching lexicography and linguistics, that, since the 1970s, have widely developed to the extent of becoming a thriving market for publishers. Looking back at the evolution of EFL dictionaries for learners and ahead to the use of corpus linguistics for the compilation of a new generation of dictionaries, this volume is of particular interest to lexicographers, although some of its references may now appear slightly outdated.